Consolidation with 90Yttrium‐ibritumomab tiuxetan after bendamustine and rituximab for relapsed follicular lymphoma. Issue 1 (7th October 2020) - Miura, Katsuhiro; Tsujimura, Hideki; Masaki, Yasufumi; Iino, Masaki; Takizawa, Jun; Maeda, Yoshinobu; Yamamoto, Kazuhiko; Tamura, Shinobu; Yoshida, Akiyo; Yagi, Hideo; Yoshida, Isao; Kitazume, Koichi; et al.
Abstract: Bendamustine and rituximab (BR) are widely used in patients with follicular lymphoma (FL) previously treated with conventional immunochemotherapy, but the role of consolidation radioimmunotherapy in these patients is unknown. This study evaluated the efficacy and safety of consolidation with 90 Yttrium‐ibritumomab tiuxetan ( 90 Y‐IT) after re‐induction therapy with BR in patients with previously treated FL. This study included adult patients with relapsed FL who had undergone one or two prior therapies. Re‐induction therapy with BR was administered every 4 weeks up to 4–6 cycles. If patients achieved at least partial response, 90 Y‐IT was administered as consolidation therapy. The primary endpoint was 2‐year progression‐free survival (PFS) after consolidation. A total of 24 FL patients (median age 60 years) who had undergone one ( n = 17) or two ( n = 7) prior treatments received BR. After BR therapy, 22 patients proceeded to consolidation with 90 Y‐IT, resulting in an overall 88% response rate to the protocol treatment. Within a median observation period of 46.8 months, the estimated 2‐year PFS rate after the consolidation among the 22 patients receiving 90 Y‐IT was 59% (95% confidence interval [CI], 38%–77%). Patients whose remission after previous treatment had lasted ≥2 years had a significantly higher 2‐year PFS rate than patients whose remission after previous treatment had been <2 years (68% vs. 33%, Wilcoxon p = 0.0211). Major adverse events during the protocol treatment and within 2 years after the consolidation were hematological toxicities, but they were generally acceptable. Consequently, the estimated 2‐year overall survival after the consolidation was 95% (95% CI, 74%–99%). In conclusion, in a subset of patients with previously treated FL, 90 Y‐IT consolidation after BR re‐induction conferred a durable remission, indicating that consolidation therapy using 90 Y‐IT may be a novel therapeutic option for patients with relapsed FL (UMIN000008793).